Alone : orphaned on the ocean - Logan, Richard D., 1942- (Titletown Pub., 2010)
Co-authored by a renowned psychologist and survival expert, this book delves into the details of how a little girl survived the at-sea murder of her family, the pod of whales who guarded her, the aftermath and recapturing of her life.